2015
DOI: 10.1016/j.sbspro.2015.01.1175
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Insights within a Blue Ocean Based on Business Intelligence

Abstract: At this moment we are seeing a confluence of practices and technologies into smarter computing capabilities that enable organizations to accomplish intelligent actions to address time-sensitive business processes and benefit from analytics. Business Intelligence processes within companies allow obtaining blue oceans where a strong growth and high business benefits are pursued through the creation of a new demand in an unknown strategic space, instead of facing competitors pursued to achieve customers in an alr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…BI applications have been ported to the Web 2.0 in search of a global platform for the consumption and publication of data and services (Hermida, Meliá, Montoyo, & Gómez, 2013). Rebón et al (2015) indicated that BI processes within companies allow obtaining competitive advantage where a strong growth and high business benefits are pursued through the creation of a new demand in an unknown strategic space, instead of facing competitors pursued to achieve customers in an already developed activity.…”
Section: Importance Of Business Intelligencementioning
confidence: 99%
“…BI applications have been ported to the Web 2.0 in search of a global platform for the consumption and publication of data and services (Hermida, Meliá, Montoyo, & Gómez, 2013). Rebón et al (2015) indicated that BI processes within companies allow obtaining competitive advantage where a strong growth and high business benefits are pursued through the creation of a new demand in an unknown strategic space, instead of facing competitors pursued to achieve customers in an already developed activity.…”
Section: Importance Of Business Intelligencementioning
confidence: 99%
“…Based on the criterion that digital marketing is a novel area of knowledge and what has been published on it is contextualized in the informational field, there is an imperative need to investigate its chronological and thematic growth in the sphere of tourism; as well as its behavior according to different geographic areas. Many authors approach the subject from different perspectives, Truong, Simmons and Palmer [4] ; Rebón, Ocariz, Gerrikagoitia and Alzua-Sorzabal [5] and Shankar et al [6] agree that digital marketing management in organizations is a key process to achieve success. Rapid changes in digital consumer behavior, require timely and sophisticated responses from tourism organizations to these consumer needs [7] .…”
Section: Introductionmentioning
confidence: 99%
“…When the company stakeholders are able to make fact-based decision using the capability of data analytics, the company will have a greater likelihood of increased revenue, cost-cutting, and improved competitive advantage. To date, data analytics has been widely adopted to support the operations in many businesses or industries like healthcare (McGlothlin and Khan 2013), electricity supply (Qiu et al 2013), manufacturing (Jesus and Bernardino 2014), railway safety management (Lira et al 2014), financial service (Chang 2014), tourism (Rebón et al 2015), education (Haupt et al 2015), monitoring of quality for web services , monitoring for quality-of-experience in high-density wireless network (Qaiyum et al 2016) and even not-for-profit organizations (Oakley et al 2015). Figure 1 depicts the entire implementation process of a typical data analytics practice (Gullo 2015).…”
Section: Introductionmentioning
confidence: 99%